Differential Characteristics of Poor and Non-Poor Communities in Malaybalay City (Asia Pacific Journal of Social and Behavioral Sciences, 2012)
Poverty is a multi-dimensional phenomenon. In this study, eight dimensions were considered: demography, economic activities, environmental sanitation, literacy and education, social welfare, food shortage and food threshold of 14,528 households of Malaybalay City, Bukidnon. Given these dimensions, discriminant analysis was used to establish the characteristics of poor and non-poor households on the basis of multiple responses on all households. The classification results reveal 87.9% of households were classified correctly into poor and non-poor groups. A Initial results further revealed that literacy and education and environmental sanitation were the strongest predictors of the group classification. Furthermore, on the basis of the classification rule developed in the study, of the identified poor households only 32.14% were recipients of the poverty reduction program of the city while 67.86% of the recipients were actually non-poor. The classification rule developed by this study did not match the classification rule of the city. The analysis of this paper is certainly not of sufficient complexity to allow a comprehensive poverty reduction strategy for Malaybalay City to be devised entirely from this result. Nevertheless, it does provide policy planners with objective measures on the distribution of goods and services for poverty alleviation that might be realized from sectoral poverty reduction strategy. Policy planners should view this result as a guide to allocate resources for poverty reduction in a more informed evidence-based manner.
Keywords: A differential characteristics, poverty, discriminant analysis